Ontology-based problem solving method for dynamic scheduling in agile manufacturing / Muhammad Firdaus Mustapha, Siti Hasrinafasya Che Hassan and Wan Salfarina Wan Husain - Mustapha, Muhammad Firdaus; Che Hassan, Siti Hasrinafasya; Wan Husain, Wan Salfarina (Research Management Institute (RMI), 2011)
Manufacturing scheduling can be defined as a process of allocating and timing resources usage in a manufacturing system to complete jobs over time. According to (Pinedo, 2005), the purpose of scheduling in manufacturing is to minimise the production time and costs, by telling a production facility of what to make, when, with which staff, and on which equipment in order to maximise the efficiency of operation and to reduce costs. In the mean time, rescheduling is performed in the manufacturing industry when changes occur to update the current schedule in order to satisfy the changes. The new schedule is typically constructed using both jobs that are included in the previous schedule but have not started processing, followed by arrival of the new jobs.